2017
DOI: 10.1039/c7cc08120k
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized deltahedral Zintl complexes Ge9R3 (R = CF3, CN, and NO2): a new class of superhalogens

Abstract: The assembly of atoms leads to the formation of clusters. These clusters have a tendency to gain their stability by forming either cations or anions. Among the anionic clusters, Zintl ions with multiple negative charges are a special type of inorganic complex generally formed from group 13, 14 and 15 elements in the periodic table. On the other hand, superhalogens are neutral molecules which have high electron affinity. Between the two different types of molecules, the former stabilized in the neutral state by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Keeping these options in mind, we have taken three different five membered heterocyclic ligands, viz., C 2 BNSHF 2 , C 2 BNSF 3 and C 2 BNO(CN) 3 with VDE values of 2.64 eV, 2.82 eV and 4.62 eV respectively. Among these ligands, C 2 BNO(CN) 3 can be assigned as superhalogen [51][52][53] due to its higher VDE than Cl. The optimized geometries of (C 2 BNSHF 2 ) 3 BÀ P( t Bu) 3 , Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping these options in mind, we have taken three different five membered heterocyclic ligands, viz., C 2 BNSHF 2 , C 2 BNSF 3 and C 2 BNO(CN) 3 with VDE values of 2.64 eV, 2.82 eV and 4.62 eV respectively. Among these ligands, C 2 BNO(CN) 3 can be assigned as superhalogen [51][52][53] due to its higher VDE than Cl. The optimized geometries of (C 2 BNSHF 2 ) 3 BÀ P( t Bu) 3 , Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Keeping these options in mind, we have taken three different five membered heterocyclic ligands, viz., C 2 BNSHF 2 , C 2 BNSF 3 and C 2 BNO(CN) 3 with VDE values of 2.64 eV, 2.82 eV and 4.62 eV respectively. Among these ligands, C 2 BNO(CN) 3 can be assigned as superhalogen [51–53] due to its higher VDE than Cl. The optimized geometries of (C 2 BNSHF 2 ) 3 B−P( t Bu) 3 , (C 2 BNSF 3 ) 3 B−P( t Bu) 3 and [C 2 BNO(CN) 3 ] 3 B−P( t Bu) 3 along with some important bond distances, formal charges on the B/P centers and the volumes of the ligand substituted LA counterparts are given in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…which were composed of Zintl ions P 7 3− , ligated with organic species. Not only superalkali but also Zintl clusters ligated with proper ligands can show superhalogen 26 nature. A DFT based study on organo-Zintl-based superatoms 27 also revealed more halogen-mimicking properties of clusters like [Ge 9 (CHO)] and [Ge 9 (CHO) 3 ].…”
Section: ■ Introductionmentioning
confidence: 99%
“…prepared a metalloid Zintl cluster (Ga 23 {N(SiMe 3 ) 2 } 11 ) and explained its stability in terms of the Jellium shell model. Recently, Reddy et al . successfully designed deltahedral Ge 9 (R) 3 (R=CF 3 , CN, and NO 2 ) complexes, which exhibit the properties of a superhalogen.…”
Section: Introductionmentioning
confidence: 99%
“…Hartig et al [21] prepared am etalloid Zintl cluster (Ga 23 {N(SiMe 3 ) 2 } 11 )a nd explained its stabilityi nt erms of the Jellium shell model. Recently,R eddy et al [22] successfully designedd eltahedral Ge 9 (R) 3 (R = CF 3 ,C N, and NO 2 )c omplexes, whiche xhibit the properties of as uperhalogen. In ar ecent review, Sun et al [23] explained how the aromaticity concept can guide the synthesis and analysiso ft he geometrical and electronics tructures of polyanionic Zintl clusters.I nspired by these works, we have attempted to make deltahedralZ intl complexesw ith organic ligands.…”
Section: Introductionmentioning
confidence: 99%